Efektivitas Perangkat Pembelajaran menggunakan Model Treffinger untuk Meningkatkan Kemampuan Berpikir Kreatif - Risa Handayani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
The availability of learning tools is one indicator the teacher has prepared a learning planproperly. However, existing learning tools have not triggered students' creative thinkingabilities. This study aims to produce learning tools by using the Treffinger learning model toimprove the mathematical creative thinking ability of junior high school students. This type ofresearch is development research. The results of this study indicate that the learning devicemeets the effective criteria. Effectiveness can be seen in the results of positive responses ofstudents namely 89.5% and the results of student learning tests on the indicator of fluencyreached 97.7%, flexibility reached 86.7%, and authenticity reached 23.5%, so the ability tothink creatively is at the level 3 (creative).